As salas multisseriadas do campo e o sistema de avaliação: identificando a realidade do Ceará - Nascimento, Fernanda Pâmela do (2024)
This research aims to analyze how the evaluation process of the multigrade classrooms in the field in Ceará is developed, based on the organization and functioning of these classrooms and the evaluation system by results, developed in the state. In this sense, it seeks to understand how this process develops, considering that the evaluations are carried out by grade/year and the classrooms are organized in multiple stages, with multiple ages and grade/year. Therefore, in this work, it is considered the reality in which the students, although attending different school years, occupy the same space in the classroom and the teachers develop lesson plans and specific evaluations for each year/grade, in addition to the classrooms (according to the year/grade) participating in the external evaluation "SPAECE" at the end of the year. This invisibility and difficulties of the multigrade classrooms leads us to seek to understand this reality, taking as a theoretical reference, the historical-dialectical materialism and the Historical-Critical Pedagogy in the sense of reflecting on the need for transformation in the development of teaching-learning, trying to contribute to a proposal for the evaluation of the multigrade classrooms in Ceará, in order to understand and transform reality. This thesis has as a research problem: Does the evaluation process developed in Ceará, applied in the schools object of the study, meet the principles of Rural Education and the reality of these classrooms, considering their organization, their functioning and the system of evaluation by results to which they are submitted? Some research questions are also established: How is the evaluation process developed in the multigrade classrooms of the Ceará countryside? Are the contents of the assessments specific to each grade? With the creation of the National Common Curricular Base (BNCC), was there any change in the content and in the way students are assessed? Is the specificity of the Countryside and its forms of production and life considered in the contents and evaluations? Do all students who are part of the multigrade classrooms participate in the external assessments? The authors and theorists who support the framework are scholars of the subject, classics and current researchers. The thesis defended is that the evaluation process developed in schools with multigrade classes in Ceará, does not contemplate the reality of schools, nor the paradigm of rural education, signals, therefore, to an evaluation proposal in rural schools, with multigrade classes, from a continuous process, developed under the materialist-historical-dialectical theoretical basis, in line with the paradigms of rural education in an emancipatory perspective. It concludes that it is necessary to develop a policy of basic education in the countryside that guarantees the intellectual elevation of teachers and students and strengthens the struggle of the rural working class.